Proceedings of China SAE Congress 2020: Selected Papers - SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
These proceedings gather outstanding papers presented at the China SAE Congress 2020, held on Oct. 27-29, Shanghai, China. Featuring contributions mainly from China, the biggest carmaker as well as most dynamic car market in the world, the book covers a wide range of automotive-related topics and the latest technical advances in the industry. Many of the approaches in the book will help technicians to solve practical problems that affect their daily work. In addition, the book offers valuable technical support to engineers, researchers and postgraduate students in the field of automotive engineering.
Intelligent & Connected Vehicles Technologies -- BEV/HEV/FCEV Technologies -- Internal Combustion Engine, Lubrication -- Environment and Emission Control -- Vehicle Dynamics and Systems Integration -- Noise, Vibration & Harshness (NVH) -- Product and Performance Technology -- Automotive Aerodynamics -- Automotive Reliability Technologies -- Advanced Transmission System and Driveline -- Vehicle Electronics Control Technologies -- Advanced Car Body Design -- Lightweight Technologies -- Advanced Vehicle Manufacturing Technologies -- Automotive Safety Technologies -- Automotive Simulation and Testing -- Technical Management.
Keywords: Vehicles; Automotive engineering; Transportation engineering; Traffic engineering; Vehicle Engineering; Automotive Engineering; Transportation Technology and Traffic Engineering; Automobiles -- Design and construction -- Congresses